Uzupełnianie ubytków zapraw w malowidłach na płótnie – przegląd materiałów i metod - Łękawa-Wysłouch, Teresa (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2010)
In the article the literature on reintegrating injuries of priming in canvas paintings has been reviewed. The criteria of selecting the materials have been discussed, the means used in that procedure have been characterised taking into consideration their division into two groups according to the types of binding media, that is fi llers based on natural binding media (glue-, emulsion-, oil-, bees wax- and bees wax and resin-based) and those based on synthetic resins (BEVA 371, polyvinyl alcohol, polyvinyl acetate, polyacrylate resins). Also the methods used to apply and to work-out the injuries have been discussed, starting form preparation of the injuries themselves, application of fi llers, levelling their surface and developing their texture.